A novel antifungal protein of Bacillus subtilis B25 - Tan, Zhiqiong (Springer International Publishing, 2013)
Bacillus subtilis B25 was isolated from banana rhizosphere soil. It has been confirmed for B25 to have stronger antagonism against Fusarium oxysporum f.sp.cubense, Additionally B25 has good inhibitory to plant pathogens, including Corynespora cassiicola, Alternaria solani, Botrytis cinerea and Colletotrichum gloeosporioides on potato dextrose agar (PDA) plates. The antagonistic substance can be extracted from cell-free culture broth supernatants by 70% (w/v) (NH4)2 SO4 saturation. Clear blank band was observed between the protein and a pathogen. The examination of antagonistic mechanism under light microscope showed that the antifungal protein of B25 appeared to inhibit pathogens by leading to mycelium and spores tumescence, distortion, abnormality. The isolation procedure comprised ion exchange chromatography on DEAE-Sephadex Fast Flow and gel filtration chromatography on SephadexG-100. The purified antifungal fraction showed a single band in sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The active fraction was identified by NanoLC-ESI-MS/MS The amino acid sequences of 17 peptides segments were obtained. The analysis of the protein suggested that it was a hypothetical protein (gi154685475), with a relative molecular mass of 38708.67 Da and isoelectric point (pI) of 5.63.